Life imprisonment in Hong Kong - Pascoe, Daniel (Life Imprisonment in Asia, 2023)
Despite the hardening local political context, life imprisonment laws and practices in Hong Kong remain relatively liberal by common law standards. This chapter first describes the legal position of life imprisonment in Hong Kong since the handover of sovereignty to the People’s Republic of China in 1997, by assessing life-eligible crimes, types of life sentences, constraints on judicial decision-making and possibilities for eventual release. The chapter then situates Hong Kong’s actual use of life imprisonment since 1997 within the worldwide practice of life imprisonment, particularly that of common law jurisdictions including England and Wales. Given the rarity of ‘de facto’ life sentences in Hong Kong, the chapter’s analysis focuses on mandatory and discretionary formal life terms pronounced by the Hong Kong courts, and their consideration by the Long-term Sentences Review Board—Hong Kong’s answer to a parole board for life-sentenced prisoners. Finally, the chapter comments on the prospective impact on life imprisonment, if any, of the recent authoritarian turn brought to Hong Kong law and politics by the Beijing-drafted National Security Law (June 2020), plans for further Basic Law article 23 legislation, and the ongoing prosecutions of anti-government protesters after major social unrest between 2014 and 2020.